Language Style in Pocky Brand Snack Product Advertisements in Japanese - Selvi Khafifah; Arza Aibonotika; Sri Wahyu Widiati (Journal of Education Technology Information Social Sciences and Health, 2024)
Pocky is a popular snack food in Japan produced by PT Glico which has expanded to various countries.  Pocky advertisements offer the advantages of their products using a unique language style.  Language style is an important aspect for packaging advertising language so that advertising objectives are achieved.  This research aims to describe the use of language styles in Pocky advertisements.  The method used is descriptive qualitative with websites and social media as data sources.  Data collection techniques in this research include reading methods and note-taking techniques.  The results of this research show that 5 language styles were found in the Pocky advertisement, namely hyperbole, metaphor, simile, personification, and asyndeton.  From the results obtained, it can be concluded that the characteristic that Pocky wants to display through the 2022 advertisement is Pocky as a special and exclusive snack with a tendency to use hyperbole to give an exaggerated effect and a dramatic impression of Pocky to increase consumer confidence value.